A Review Paper on Wireless Sensor Network (International Journal of Innovative Research in Computer Science & Technology, 2022)
Security is one of the most essential things  to consider if sensor networks are to reach their full  potential. Even more innocuous applications, such as home  health monitoring, habitat monitoring, and subsurface  research, need anonymity. WSNs are ideal for detecting  environmental, biological, or chemical hazards over broad  regions, but deliberately generated false alarms may render  the system useless. The topics of habitat monitoring and  traffic management are discussed. WSNs are network of  physically spread and customized instruments for  monitoring and document atmospheric factors and transmit  the data to a central location. WSNs may measure  temperatures, sounds, particulate emissions, moisture, and  winds, between other things. Sensor’s node construction  presents a number of technological issues, including  networks scanning, management, and forwarding,  collaboration signals and executive function, task  management and queries, and privacy. Furthermore, the  essay goes through some recent sensing node studies  discoveries, including localised techniques and guided  dispersion, distribution surveillance in mobile ad hoc  systems, and distribution classification using local  suppliers.
Keywords: Data; Information; Network; Sensor; Wireless